Car buying behaviour in Klang Valley / Azrin Nur Farah Abdullah Din - Abdullah Din, Azrin Nur Farah (Faculty of Business and Management, 2011)
The purpose of this paper is to investigate and study on the factors influencing consumers’ buying behavior towards cars.